Experimental Effect of Angle Variation and Speed Welding Filler Using Vertical Adaptive Sliding System In SMAW Welding - Nusbir, Yohanes; Sianipar, Alfrets Marade (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2018)
In each welding technology each has advantages in accordance with the placement of its implementation. One of the welding technologies is the SMAW (shield metal arc welding) has an advantage over the current and the welding angle can be varied, and the penetration width of the electrode fuses can be adjusted. This research uses SMAW welding machine with sliding adaptive vertical system design for proper welding speed. this study varied the angle and speed of welding to determine the welding results of SMAW welding machine with sliding adaptive vertical system. In this study the characteristics of welding results based on visual observation and mechanical properties using tensile test. The parameters are varied angles 600, 650, and 750 and welding speed controlled arduino uno with a stepper round of 1.5 Rpm, 1.75 Rpm, and 2 Rpm. The material used is a low carbon steel, using a hometown V with 60 hill angle. In this study the highest metal tackling region is the tensile strength of 571.35 MPa and the lowest value is 475.52 MPa with the number of specimens varied by 9 specimens. Micro welding structure is determined by many factors including heat input, current strength, welding speed, and cooling rate. In this study the HAZ area has a larger grain structure than base metal and weld metal.